Metabolic reprogramming and two-compartment tumor metabolism: Opposing role(s) of HIF1α and HIF2α in tumor-associated fibroblasts and human breast cancer cells - Chiavarina, Barbara (Landes Bioscience, 2012)
Hypoxia-inducible factor (HIF) 1α and 2α are transcription factors responsible for the cellular response to hypoxia. The functional roles of HIF1α and HIF2α in cancer are distinct and vary among different tumor types. The aim of this study was to evaluate the compartment-specific role(s) of HIF1α and HIF2α in breast cancer. To this end, immortalized human fibroblasts and MDA-MB-231 breast cancer cells carrying constitutively active HIF1α or HIF2α mutants were analyzed with respect to their metabolic function(s) and ability to promote tumor growth in an in vivo setting. We observed that activation of HIF1α, but not HIF2α, in stromal cells promotes a shift toward aerobic glycolysis, with increased L-lactate production and a loss of mitochondrial activity. In a xenograft model, HIF1α-activated fibroblasts promoted the tumor growth of co-injected MDA-MB-231 cells without an increase in angiogenesis. Conversely, HIF2α-activated stromal cells did not favor tumor growth and behaved as the empty vector controls. Similarly, activation of HIF1α, but not HIF2α, in MDA-MB-231 cells promoted a shift toward aerobic glycolysis, with increased glucose uptake and L-lactate production. In contrast, HIF2α activation in cancer cells increased the expression of EGFR, Ras and cyclin D1, which are known markers of tumor growth and cell cycle progression. In a xenograft model, HIF1α activation in MDA-MB-231 cells acted as a tumor suppressor, resulting in an almost 2-fold reduction in tumor mass and volume. Interestingly, HIF2α activation in MDA-MB-231 cells induced a significant ~2-fold-increase in tumor mass and volume. Analysis of mitochondrial activity in these tumor xenografts using COX (cytochrome C oxidase) staining demonstrated elevated mitochondrial oxidative metabolism (OXPHOS) in HIF2α-tumors. We conclude that the role(s) of HIF1α and HIF2α in tumorigenesis are compartment-specific. HIF1α acts as a tumor promoter in stromal cells but as a tumor suppressor in cancer cells. Conversely, HIF2α is a tumor promoter in cancer cells. Mechanistically, HIF1α-driven aerobic glycolysis in stromal cells supports cancer cell growth via the paracrine production of nutrients (such as L-lactate) that can “feed” cancer cells. However, HIF1α-driven aerobic glycolysis in cancer cells inhibits tumor growth. Finally, HIF2α activation in cancer cells induces the expression of known pro-oncogenic molecules and promotes the mitochondrial activity of cancer cells.